Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 3. Beitrag. Lepidoptera: Tineidae. - Petersen, Günther (Contributions to Entomology = Beiträge zur Entomologie, 1963)
As a contribution to the Lepidopterous fauna of Albania there is presented a list of the Tineid species which were found during the recent expedition of the Deutsches Entomologisches Institut to this country. The number of species was completed by a reinvestigation of the material collected by Predota & Zerny on their trip to Northern Albania in 1918. With special reference to the author's studies on the distribution of Tineid moths of the adjoining countries the result enunmerates 44 species of this family, including as new to science Infurcitinae albanica and the hitherto unknown female of Novotinea carbonifera (Wlsm.)Nomenclatural Actsalbanica Petersen, 1963 (Infurcitinea), spec. nov.exquisita Gozmány, 1960 (Tinea), syn. n. of Tinea basifasciella Ragonot, 1895